The work of administration in Nigeria : case studies - Murray, D. J.; University of Ife. (Nigeria : Published for the Institute of Administration, University of Ife, Nigeria by Hutchinson, 1969)
This book contains five studies of administrative episodes. They are descriptive accounts which seek both to illuminate the problems facing administrators in Nigeria and to throw light on how those problems are being tackled.
Includes bibliographical footnotes.
hza 10/07/2018
Loans
Keywords: Administrative regulations; Nigeria